INCLUSIVE EDUCATION EFFORTS FOR CHILD REFUGEES IN INDONESIA WITHIN MULTI-STAKEHOLDER PARTNERSHIP (MSPS) FRAMEWORK - Sri Suwartiningsih (Indonesian Journal of International Relations, 2022)
This research aims to explain various inclusive education efforts for child refugees in Indonesia within Multi-Stakeholder Partnerships (MSPs) framework involving the government, international organizations, non-governmental organizations, and academic sector. By using qualitative research methods and neoliberalism theory, the results show that there are various MSPs collaborations to implement inclusive education for child refugees in Indonesia. These collaborations include collaboration between UNHCR Indonesia, Dompet Dhuafa, Human Initiative, and PKBM schools to provide preparatory classes before entering national schools, collaboration between UNHCR and universities, as well as collaboration between IOM Indonesia and the government through the Rudenim to provide home-schooling for refugees. It concluded that inclusive education efforts for child refugees in Indonesia have been carried out quite well by several actors, but this commitment must continue to be improved by increasing national regulations related to the refugee education and providing legal certificates for refugees who have completed their education child refugees; inclusive education, Multi-Stakeholder Partnership; cross-sector collaboration.